Nilai Kearifan Lokal Tradisi Nandong Di Simeulue Dan Fungsinya Pada Pewarisan Budaya Bagi Masyarakat Setempat - Aulia Rahman; Okhaifi Prasetyo; Yulisa Rahmatin; Imam Hadi Sutrisno; Madhan Anis (Publikasi Berkala Pendidikan Ilmu Sosial, 2024)
The Nandong tradition is an abstract expression representing Simeulue's unique cultural heritage. This research aims to describe the local wisdom values of the Nandong tradition in Simeulue and their function in cultural inheritance for the local community. This research was conducted using a qualitative ethnographic approach. This research shows that the Simeulue people have various oral traditions, including the nanga-nanga and Dandong traditions. These traditions have meaningful values passed down by their ancestors from generation to generation and are instilled in the daily life of the Simeulue people. , these values are the delivery of moral messages, advice, attitudes of respect, responsibility, and resilience; these values cannot be separated from religious teachings. The cultural inheritance of the local wisdom values of the Nandong tradition is to perform Nandong arts at Simeulue birthday events and cultural festivals, welcoming guests as well as at weddings and circumcisions of the apostles and inviting the public to watch every Nandong performance so that people understand Nandong. Nandong art is also inherited through Nandong poetry, which contains important meaning, namely the advice in it, which is then conveyed to the public regarding knowledge of the signs of natural phenomena. However, the preservation of Nandong culture has begun to fade due to the development of modern musical instruments, so local culture is increasingly rarely displayed.